ASPEK SANITASI DAN HYGIENE DALAM PROSES PEMBUATAN SWISS ROLL DI TRIPLE COMBO BOGOR - latifa, Mutia nurul; Setiawati, Rahmi (UI Scholars Hub, 2018)
The development of tourism in Indonesia is currently experiencing a significant increase every year. This also affects the industrial development of food and beverage services. These services can usually be a restaurants coffee shops and cake shops. In general Journal of Indonesian Tourism and policy Studies Vol. 3 No. 1 ISSN 2541-5360 restaurants serve processed foods and beverages cooked by the chefs. But in the restaurant Triple Combo also sell a variety of cakes that attract the attention of the public. One of cake enough to be the attraction for tourists who visit is swiss roll cake. To keep the quality of swiss roll cake the main thing to be considered is the aspect of sanitation and hygiene in the process of making it. There are several things that must be considered in this case is the health and hygiene of the chef, the cleanliness of the tools, and the cleanliness of the manufacture site. This is due to the health of consumers who will buy and consume these foods. In collecting data writer use qualitative method in the form of interview and observation. The results of this study indicate that the manufacture of swiss roll cake in Triple Combo has aspects of sanitation and hygiene are quite good and very noticed by the cook.